Non-alcoholic Fatty Liver & its Anthropometric Measurement - Alam, Azmeri; Raihan, M Al Masudur; Sadiya, Salma; Begum, Asma; Zeba, Zebunnessa (Islami Bank Medical College Journal, 2013)
DOI: http://dx.doi.org/10.3329/ibmcj.v2i1.17311 IBMC J 2011; 2(1): 14-16